Classification of the spectral fine structure in auroral kilometric radiation - Taubenschuss, U.; Fischer, G.; Pisa, D.; Santolík, O.; Soucek, J. (My University, 2023)
Auroral Kilometric Radiation (AKR) is generated by unstable energetic electron populations in the auroral region of Earth's magnetosphere. A mechanism known as the cyclotron maser instability amplifies weak background radiation at the expense of particle energy. However, this instability alone can not explain frequent observations of AKR spectral fine structures when recorded with sufficiently high time and frequency resolution. We will analyse observations of AKR from the Cluster Wideband Receiver and give an overview of the different types of spectral fine structures found in this dataset for the years 2002 and 2003. A classification scheme is introduced, and the occurrence rate for each class of fine structure is investigated in a statistical analysis. Finally, possible generation mechanisms will be discussed in relation to the observations.
Planetary, Solar and Heliospheric Radio Emissions IX
PUBLISHED